South Park City, Colorado - Cechner, Frank A ([Place of publication not identified] : Photographers of the West Publishers, 1987)
Black and white photographs taken by the author of old buildings in South Park City in the 1980s.
Keywords: South Park (Colo.) -- Pictorial works; Photobooks